Peningkatan Pengetahuan Ibu dalam Pemanfaatan Buku KIA terhadap Deteksi Dini Tumbuh Kembang Anak Usia Dini - Revinel Revinel; Dina Sulviana Damayanti; Aning Subiyatin (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
A very important period to attention for a child's growth and development so that any abnormalities in their growth and development can be detected as early as possible is the age of 0 to 5 years, this period is often also called the "Golden Age" phase.. The aim of this community service is to increase mothers' knowledge, understanding and skills in utilizing the KIA book for early detection of early childhood growth and development so as to reduce the incidence of stunting. The event featured a question-and-answer session attended by 18 mothers with toddlers living at the Kemayoran District Community Health Center. The media used are KIA guidebook s and banners, success indicators are seen from the results of the pretest and posttest conducted before and after providing the material. The results of this activity showed an increase in mothers' knowledge and abilities before and after being given education on the use of KIA guidebook in early detection of early childhood growth and development.